Collaborative Online International Learning: Technology Applied to Education - Cipagauta Moyano, Marisol Esperanza (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
As a strategy for internacionalization of the syllabus, COILs or Collaborative Online International Learnings have positioned themselves as an alternative for the promotion of intercultural competences, free of charge and without moving abroad. This article shares the experience of a COIL developed by teams of students from Colombia and Peru, based on a research idea in the field of education, describing the step-by-step process and analyzing its contribution to the teaching, learning and assessment process from the participants' perspectives.